A Study of Hospital Competition in Yogyakarta City with Huff’s Gravity Model and Valuation Methods - Vieira, Isabel; Asmara, Gea Dwi (Universitas Ahmad Dahlan, Yogyakarta, 2024)
This analysis was conducted to identify the level of hospital competition in Yogyakarta City. The object of this study is 12 hospitals in Yogyakarta City. The analytical tools in this study consist of two methods. The ?irst method is the Huff’s Gravity Model used to estimate the probability of visits to each hospital so that the competition between hospitals can be known. The second method is the valuation method using the income approach to calculate the potential value of the hospital. The results of this study show that the largest visit probability and potential value are owned by RS PKU Muhammadiyah Yogyakarta with a probability value of 19.91% and a potential value of IDR 8,493,747,933,578 for an optimistic estimate, IDR 3,370,534,894,277 for a moderate estimate, and IDR 1,400,068,340,700 pessimistic estimate. The contribution of this research can be considered in making investment decisions, especially in planning the establishment of a new hospital or expanding the capacity of an existing hospital. For investors who will invest in the hospital industry, they should look for locations that are easily accessible and avoid building hospitals with lower types near hospitals with high types; this will affect the level of probability of visits to the hospital itself. If the level of visit opportunity is low, then the potential value that will be obtained will also be low.